2020
DOI: 10.3917/reco.711.0109
|View full text |Cite
|
Sign up to set email alerts
|

Les déterminants de la mobilisation des Gilets jaunes

Abstract: Les documents de travail ne reflètent pas la position du CREST et n'engagent que leurs auteurs. Working papers do not reflect the position of CREST but only the views of the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…Hungarian populist Viktor Orban has been strongest in the countryside (Rachman, 2018). And in France, the Gilet Jaune protesters have travelled from peripheral rural areas to Paris to protest against Macron's policies (Boyer et al, 2019). Economic geographers have suggested that this might, in part, reflect patterns of uneven development and an urban-focused growth model where core areas and cities have done better than towns and the periphery (Rodríguez-Pose, 2018;Gordon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hungarian populist Viktor Orban has been strongest in the countryside (Rachman, 2018). And in France, the Gilet Jaune protesters have travelled from peripheral rural areas to Paris to protest against Macron's policies (Boyer et al, 2019). Economic geographers have suggested that this might, in part, reflect patterns of uneven development and an urban-focused growth model where core areas and cities have done better than towns and the periphery (Rodríguez-Pose, 2018;Gordon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the movement has received attention in the news and social media, a theoretical analysis of the factors explaining the emergence and continued persistence of the movement is only slowly emerging. Nevertheless, despite a scarcity of empirical research (for exceptions, see Bennani, Gandré & Monnery, 2019;Boyer at al., 2019), it is clear that the Yellow Vest movement deserves attention from social scientists. As an initially spontaneous and grassroots rural uprising without apparent organizational structures or leaders, the Yellow Vests has led to substantial policy change and concessions on the part of the French government, changing the political landscape in France.…”
mentioning
confidence: 99%
“…Relevant because this is the level at which certain regional development policies in the health, social, education and planning sectors are deployed. It is also relevant because people are attached to this level, as illustrated by various anecdotes: strong opposition to the plan to remove the department number from vehicle registration plates in 2008, strong proportion of gilet jaunes Facebook groups that include a reference to the department (20% according to Boyer et al, 2019), etc. Historical reconstructions of income at smaller scales, such as commune or canton, are possible, but these come up against difficult issues surrounding the spatial development of these units, which was very significant over the 20th century, and the disconnection between the places where the people live and where they work.…”
Section: * * *mentioning
confidence: 99%